Market adoption and diffusion of fecal sludge-based fertilizer in developing countries: crosscountry analyses - Otoo, Miriam; Gebrezgabher, Solomie A.; Danso, G.; Amewu, Sena; Amirova, Iroda (International Water Management Institute, 2018)
The safe recovery of nutrients from our waste streams allows us to address the challenges of waste management and soil nutrient depletion conjointly. Commercialization of waste-based organic fertilizers such as FortiferTM (fecal sludge-based co-compost) has the potential to generate significant benefits for developing economies via cost recovery for the sanitation sector and the provision of an alternative agricultural input for smallholder farmers. To guide future FortiferTM businesses, this report presents examples of detailed market assessments, based on farmers’ perceptions, attitudes and willingness-to-pay (WTP) for a pelletized and non-pelletized FortiferTM co-compost. The research was conducted in the Greater Accra and Western regions in Ghana, and in and around Kampala (Uganda), Bangalore (India), Hanoi (Vietnam), and Kurunegala (Sri Lanka). Cross-country analyses helped to understand the effects of market drivers and, where possible, capture lessons learned for knowledge sharing.